Guantánamo Frames - Boguska, Rebecca (2022)
For the last twenty years, the Guantánamo Bay detention camp has not just been a military prison and security facility, but also a site of media production. Films, photographs, and documents have continued to emerge from the camp and become the focus of fierce legal and political battles, as well as intense moral anguish. This book looks at how the US Department of Defense has struggled, and often failed, to control the public perception of these media objects through complex, layered framing devices. It traces how small ruptures in the Department's framings have provided openings for critical interventions from various fields - ranging from journalism and human rights law to the arts. Guantánamo Frames thus lays the groundwork for a critical reappraisal of the entanglement of media, violence, and the security state in a broader sense.